Production of public service announcement for DENR Region XI regarding air pollution through car stickers - Rico, Joan Dale L.
This print production was conducted to present car sticker designs as alternative mediums to the public awareness tools of DENR Region XI. This aims to create a more effective visual communication tool that will serve its aesthetic purposes and at the same time, as a public service announcement that will make it appealing to its target audience, the Davaoeños, and encourage them to stop air pollution and aim for clean air. This study was conducted through a creative process which consists of Pre-production, Production and Post-Production Process. This includes the application of the elements of design, typography, concepts of good design and visual relationships. The main factors considered are the shape, colors, texts and images used in the sticker designs. The Design Criticism Model and the suggestions from the employees of DENR XI Regional Public Affairs Office were considered as guide in the evaluation of the car stickers as an effective visual communication tool. Nine(9) sticker designs were presented according to three slogans: a) HELP SAVE MOTHER EARTH; b) BREADTH CLEAN AIR; and c.) TREES = AIR POLLUTION SOLUTION. There are 3 sticker designs for each slogan ? having a single concept or purpose ? to encourage the public to stop air pollution and strive for clean air. This production was able to present tips on how to produce effective sticker designs. This concludes that each element has its own meaning and function which should be carefully applied as it greatly affects the entire design. This recommends that careful consideration of the elements should be applied in designing print media tools. Stickers should also be used because they cost less than the posters and that they can be labeled on cars which travel the message anywhere. This production will help the employees of the DENR XI RPAO to further enhance their publicity tools
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Media arts